Efficacy of holmium laser versus pneumatic lithotripsy for mid and distal ureteric stones above 10 mm size - Arvind Arvind; Sudipta Kumar Singh; Partha Protim Mondal; Shashi Kant Tewary; Ankit Agarwal; Apurv Shukla; Ranjan Kumar Dey; Shiva Manohar Dutta (Asian Journal of Medical Sciences)
Background: Over the past decade, ureteral stone treatment has evolved significantly. Pneumatic lithotripsy is common but prone to stone migration. Holmium laser use has increased due to fewer complications and lower stone migration rates.